SEMANTIC SHIFT IN ENGLISH AI-RELATED NEOLOGISMS (SCIENCE TIME JOURNAL, 2026)
The rapid development of artificial intelligence technologies has significantly influenced the lexical system of the English language. New AI-related neologisms emerge not only through word formation processes but also through semantic transformation of already existing lexical units. This article investigates semantic shifts in contemporary English AI-related neologisms and analyzes howtechnological discourse changes the meanings of common lexical items. The study employs semantic, descriptive, and contextual analysis methods to examine neologisms actively used in digital communication, social media, and technological discourse. The findings reveal that AI-related vocabulary demonstrates intensive metaphorization, terminologization, and semantic broadening. Words such as “hallucination,” “prompt,” “training,” and “agent” have acquired new semantic dimensions under the influence of artificial intelligence technologies. The research highlights the role of AI discourse in accelerating lexical innovation and semantic evolution in modern English.